STRATEGY OF MARKETING LOCAL HYDROPONIC VEGETABLE IN PONTIANAK - Santi, Santi; Dolorosa, Eva; Imelda, Imelda (Jurnal Sains Pertanian Equator, 2019)
AbstractThe demand for hydroponic vegetables is quite a lot, producers are also starting to increase, so it needs a strategy for the hydroponic market. The purpose of this study is to formulate a marketing strategy by identifying internal strengths and weaknesses, as well as external opportunities and threats of hydroponic vegetable business. Data collection was carried out by distributing questionnaires, interviews and direct observation of 25 respondents. Analysis of research data using SWOT analysis. The results showed that the position of the hydroponic vegetable marketing strategy in Pontianak City in mapping the strategic environment (internal and external environment) was in the first (one) quadrant, which supported aggressive growth policies (Growth Oriented Strategy) or used the Strengths-Opportunities strategy (SO Strategy). The SO strategy is to optimize and utilize technology development as best as possible to attract potential customers, maintain and improve product quality to meet consumer needs, and expand the distribution and marketing network of hydroponic vegetables. Keywords: Hydroponic Vegetables, SWOT, marketing Strategy.